2016
DOI: 10.1074/jbc.m115.678995
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Kv1.3 Potassium Channels-induced Proliferation

Abstract: Changes in voltage-dependent potassium channels (Kv channels) associate to proliferation in many cell types, including transfected HEK293 cells. In this system Kv1.5 overexpression decreases proliferation, whereas Kv1.3 expression increases it independently of K ؉ fluxes. To identify Kv1.3 domains involved in a proliferation-associated signaling mechanism(s), we constructed chimeric Kv1.3-Kv1.5 channels and point-mutant Kv1.3 channels, which were expressed as GFP-or cherry-fusion proteins. We studied their tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…Packaging cells were transfected with 20µg of retroviral plasmid DNA encoding MSGV-Thy1.1, MSGV- Kcna3 -Thy1.1, MSGV- Kcna3 -Thy1.1 (W389F) (referred to as Kcna3_PD ) 25, 40, MSGV- Ppp2r1a (K416E) -Thy1.1 (referred to as PP2A_DN41,42), MSCV-IRES-Thy1.1 (pMIT), or pMIT Akt1- CA43 where indicated along with 6µg pCL-Eco plasmid DNA using 60µL Lipofectamine 2000 in OptiMEM (Invitrogen) for 8 hours in antibiotic-free media. Media was replaced 8h after transfection and cells were incubated for a further 48 hours.…”
Section: Materials and Methods (Online)mentioning
confidence: 99%
“…Packaging cells were transfected with 20µg of retroviral plasmid DNA encoding MSGV-Thy1.1, MSGV- Kcna3 -Thy1.1, MSGV- Kcna3 -Thy1.1 (W389F) (referred to as Kcna3_PD ) 25, 40, MSGV- Ppp2r1a (K416E) -Thy1.1 (referred to as PP2A_DN41,42), MSCV-IRES-Thy1.1 (pMIT), or pMIT Akt1- CA43 where indicated along with 6µg pCL-Eco plasmid DNA using 60µL Lipofectamine 2000 in OptiMEM (Invitrogen) for 8 hours in antibiotic-free media. Media was replaced 8h after transfection and cells were incubated for a further 48 hours.…”
Section: Materials and Methods (Online)mentioning
confidence: 99%
“…K V 1.3 is positively associated with apoptosis in different types of cells, including retinal ganglion cell (Jimenez-Perez et al, 2016), lymphocytes (Bock et al, 2002; Valencia-Cruz et al, 2009), and various cancer cells (Abdul and Hoosein, 2006; Brevet et al, 2008; Brevet et al, 2009). In agreement with these studies, our results showed Tat-induced apoptosis in cultured Ols was attenuated either by knockdown K V 1.3 gene or by specific K V 1.3 antagonists, but not by a K V 2.1 antagonist (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human VSM cells also confirm a role for K V 1.3 in proliferation (Cheong et al, 2011; Cidad et al, 2015). Interestingly, K V 1.3 may contribute to VSM proliferation by ion-permeation-independent mechanisms (Cidad et al, 2012; Cidad et al, 2015; Jimenez-Perez et al, 2016). The pro-proliferative effects of K V 1.3 are mediated by voltage-dependent exposure of key residues in the channel’s C-terminus (Tyr-447 and Ser-459) (Jimenez-Perez et al, 2016).…”
Section: K+ Channels and Vsm Proliferationmentioning
confidence: 99%
“…H. Liu et al, 2009; Mahaut-Smith, Martinez-Pinna, & Gurung, 2008; Okada, Yanagisawa, & Taira, 1993; Urena, del Valle-Rodriguez, & Lopez-Barneo, 2007; Yamagishi, Yanagisawa, & Taira, 1992; Yamamura, Ohya, Muraki, & Imaizumi, 2012; Yanagisawa, Yamagishi, & Okada, 1993). Potassium channels also contribute to the regulation of proliferation of VSM cells through membrane potential-dependent (Bi et al, 2013; Miguel-Velado et al, 2005; Miguel-Velado et al, 2010) and membrane potential-independent mechanisms (Cidad et al, 2012; Cidad et al, 2015; Jimenez-Perez et al, 2016). …”
Section: Introductionmentioning
confidence: 99%